2020
DOI: 10.1093/advances/nmz094
|View full text |Cite
|
Sign up to set email alerts
|

Farm to School Activities and Student Outcomes: A Systematic Review

Abstract: Farm to school programs (F2SPs) operate in 42% of school districts and are supported in part through federal and state policies as well as philanthropic funding. Although research evaluating the effects of farm to school–related activities on student outcomes is growing, a systematic review of the results and thus a synthesis of implications for future programming have not occurred. The primary objective of this systematic literature review is to summarize and evaluate studies on student outcomes associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…The feasibility of classroom-based farm-to-school programs has previously been questioned [23]. Yet, the teachers in the current study reported that the intervention was feasible and acceptable, as evidenced by their continuation of the intervention without researcher involvement the following year.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The feasibility of classroom-based farm-to-school programs has previously been questioned [23]. Yet, the teachers in the current study reported that the intervention was feasible and acceptable, as evidenced by their continuation of the intervention without researcher involvement the following year.…”
Section: Discussionmentioning
confidence: 69%
“…Little is known about how nutrition and food systems education impact academic outcomes [44,45]. In order for more schools to incorporate these topics into their curricula, more evidence is needed to link to educational outcomes [23,45]. The teachers in our study were motivated by the high quality writing and group activity assignments submitted by their students during the intervention; this perceived impact on student academic performance likely influenced the teachers’ desire to continue the program without researcher support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review examining the effectiveness of farm to school programs and activities reported that studies consistently show positive impacts on student food and nutrition-related knowledge. In addition, most studies suggest a positive relationship between farm-to-school activities and healthy food selection during school meals, nutrition self-efficacy, and willingness to try fruits and vegetables [3]. The impact of farm-to-school activities on fruit and vegetable consumption and preference is unclear [3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most studies suggest a positive relationship between farm-to-school activities and healthy food selection during school meals, nutrition self-efficacy, and willingness to try fruits and vegetables [3]. The impact of farm-to-school activities on fruit and vegetable consumption and preference is unclear [3].…”
Section: Introductionmentioning
confidence: 99%